1990
DOI: 10.1007/bf00164748
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of phenolic effluents by soluble and immobilized phenol oxidases

Abstract: Colour removal from phenolic industrial effluents by phenol oxidase enzymes and white-rot fungi was compared. Soluble laccase and horseradish peroxidase (HRP) removed colour from pulp mill (E), cotton mill hydroxide (OH) and cotton mill sulphide (S) effluents, but rapid and irreversible enzyme inactivation took place. Entrapment of laccase in alginate beads improved decolorization by factors of 3.5 (OH) and 2 (E); entrapment of HRP improved decolorization by 36 (OH), 20 (E) and 9 (S). Beads were unsuitable for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Eighty-three percent of the protein bound to the carrier, corresponding to 0.13 mg g −1 alumina and 72% of the laccase activity was retained on the carrier material. Previously, between 70 and 98% of the protein immobilised and 67-96% of laccase activity, recovery was reported with different carrier materials [52][53][54]. Out of a number of different carrier materials previously tested for laccase immobilization such as activated carbon [55], Eupergit ® C [56], Sepharose [57], silica-based matrices [58] and porous glass [53,59] only alumina was used in this study as it seems to be more suitable for application in dye decolourization, due to its mechanical stability.…”
Section: Redyeingmentioning
confidence: 99%
“…Eighty-three percent of the protein bound to the carrier, corresponding to 0.13 mg g −1 alumina and 72% of the laccase activity was retained on the carrier material. Previously, between 70 and 98% of the protein immobilised and 67-96% of laccase activity, recovery was reported with different carrier materials [52][53][54]. Out of a number of different carrier materials previously tested for laccase immobilization such as activated carbon [55], Eupergit ® C [56], Sepharose [57], silica-based matrices [58] and porous glass [53,59] only alumina was used in this study as it seems to be more suitable for application in dye decolourization, due to its mechanical stability.…”
Section: Redyeingmentioning
confidence: 99%
“…There are several reports about the leakage of enzymes from porous polymeric matrices, calcium alginate gel, 18,20,21 poly(vinyl) hydrogel 22 and sol-gel. 23 In order to prevent the leaching of enzymes from physically entrapped gels, a number of attempts have been made to increase the molecular dimension of the enzymes prior to their entrapment.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Calcium alginatemediated entrapment has attracted much attention in the detoxification of phenolic compounds present in industrial effluents. 18 Recently some workers have reported that pectin beads were significantly more stable than alginate beads. 19 The cost of pectin is further making the immobilization procedure more expensive.…”
Section: Introductionmentioning
confidence: 99%
“…However, laccase and peroxidase are rapidly inactivated during the reaction demonstrating that both the cost of the enzymes and their operational stability are of paramount importance. Laccase and peroxidase were previously shown to remove colour from industrial phenolic effluents, and this activity was improved by copolymerisation with L-tyrosine and slow release of enzyme from alginate beads (Davis and Burns 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafiltration (PM 10 and 30 membranes -Amicon, Stonehouse, Glos., UK) revealed that colour is associated predominantly with compounds from 1 x 103 to 2x 105 Da. Colour was measured at 465 nm as described previously (Davis and Burns 1990).…”
Section: Introductionmentioning
confidence: 99%